Factorize : x4+ 1/x4 +1
-
i) I suppose your question is to factorize: (x^4) + {1/(x^4)} + 1
ii) Adding and subtracting 1, it is: (x^4) + {1/(x^4)} + 2 - 1
==> = (x² + 1/x²)² - 1
iii) Applying a² - b² = (a + b)(a - b),
this is = {x² + (1/x²) + 1}*{x² + (1/x²) - 1}
ii) Adding and subtracting 1, it is: (x^4) + {1/(x^4)} + 2 - 1
==> = (x² + 1/x²)² - 1
iii) Applying a² - b² = (a + b)(a - b),
this is = {x² + (1/x²) + 1}*{x² + (1/x²) - 1}
-
x^4+ 1/x^4 +1
= x^44 + 2 + 1/x^44 + 1 – 2
= x^4 + 2 + 1/x^4 – 1
= (x^2 + 1/x^2)² – (1)²
= (x^2 + 1/x^2 + 1)(x^2 + 1/x^2 – 1)
-----
= x^44 + 2 + 1/x^44 + 1 – 2
= x^4 + 2 + 1/x^4 – 1
= (x^2 + 1/x^2)² – (1)²
= (x^2 + 1/x^2 + 1)(x^2 + 1/x^2 – 1)
-----
-
x^4+ 1/x^4 +1
= 1/x^4(x^8 + x^4 + 1)
= 1/x^4(x^4 - x^2 + 1)(x^4 + x^2 + 1)
= 1/x^4(x^2 - x + 1)(x^2 + x + 1)(x^4 - x^2 + 1)
= 1/x^4(x^8 + x^4 + 1)
= 1/x^4(x^4 - x^2 + 1)(x^4 + x^2 + 1)
= 1/x^4(x^2 - x + 1)(x^2 + x + 1)(x^4 - x^2 + 1)
-
((x^2-x+1)(x^2+x+1)(x^4-x^2+1))/x^4